Analisis Kinerja Keuangan Menggunakan Metode Dupont System pada PT. Uni-Charm Indonesia Tbk Tahun 2020–2024 - Nabira Araminta Wardiyah; Luthfiyah Alvian; Septyani Eka Putri; Deby Rizqi Apriliyani (AKUNTANSI 45, 2026)
Financial performance is an important indicator used to assess a company’s ability to manage resources effectively and generate profits for shareholders. This study aims to analyze the financial performance of PT Uni-Charm Indonesia Tbk for the 2020–2024 period using the DuPont System method. This method was chosen because it is able to integrate aspects of profitability, asset activity, and leverage in measuring the company’s return on equity. The study uses a quantitative approach with a descriptive method. The data used are secondary data obtained from the annual financial statements of PT Uni-Charm Indonesia Tbk for the 2020–2024 period. The analysis was carried out through the calculation of Net Profit Margin (NPM), Total Asset Turnover (TATO), Equity Multiplier (EM), and Return on Equity (ROE). The results showed that the company’s financial performance fluctuated during the study period. The highest ROE value occurred in 2021 at 9.8%, while the lowest value occurred in 2024 at 6.0%. ROE fluctuations are influenced by changes in the three DuPont components, but the most dominant factor is Net Profit Margin (NPM). Meanwhile, TATO demonstrated relatively good asset utilization effectiveness, despite a decline at the end of the study period. EM tended to decline, indicating the company’s reduced reliance on debt-based funding. Based on the analysis, profitability was the primary factor influencing PT Uni-Charm Indonesia Tbk’s financial performance during the 2020–2024 period.